Kajian Ekonomi Syariah Perspektif Filsafat Islam - Yunadi, Ahmad (Universitas Alma Ata, 2022)
This research is a library research by using books and other literatures as the main object. The study in this paper provides a clear, objective, analytical and critical overview of the existing phenomena regarding the development of Islamic economics in Indonesia in the perspective of Islamic philosophy. Currently, there are still some discrepancies between the concept and its application in Islamic Economics. It took a lot of time to find meaning from the concept of Islamic economics through the Islamic law/maqasid sharia approach. The search for meaning is of course through inquiries by involving many researchers both from insiders and outsiders. The concept of maqasid shari'ah is strongly influenced by interpretation, perspective, educational background and depth of religious knowledge.In the study of the philosophy of the Islamic sciences, one of the efforts to break the stagnation of Islamic economic concepts and thinking is through the deconstruction of critical thinking with a critical paradigm. It is needed to avoid logocentrism (centered on its own logos/way of thinking). Each mahzab of Islamic economics should be aware that religious understanding from nash is essentially only one possible meaning of the many other possible meanings hidden behind the nash. This is to avoid the reality of the sacralization of each other's understanding so that it triggers conflict with the understanding of others. That way, the common thread of the concept of Islamic economics can be found together to be a reference for practice its field.Keywords; Economics, Islam, Maqasid Sharia, Philosophy.